2012
DOI: 10.2147/ijn.s28460
|View full text |Cite
|
Sign up to set email alerts
|

Poly-l-lysine-coated magnetic nanoparticles as intracellular actuators for neural guidance

Abstract: Purpose: It has been proposed in the literature that Fe 3 O 4 magnetic nanoparticles (MNPs) could be exploited to enhance or accelerate nerve regeneration and to provide guidance for regenerating axons. MNPs could create mechanical tension that stimulates the growth and elongation of axons. Particles suitable for this purpose should possess (1) high saturation magnetization, (2) a negligible cytotoxic profile, and (3) a high capacity to magnetize mammalian cells. Unfortunately, the materials currently availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…In the present study, PLL was used to modify SPIONs via electrostatic interactions. PLL-SPIONs showed positive charges as reported previously (Riggio et al, 2012). In addition, it has been reported that no detectable uptake of iron was found for dextran-coated SPIONs with concentrations <0.5 mg/ml after 48 h incubation, and approximately half of the cells were abundantly labeled at 2 mg/ml (Dunning et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, PLL was used to modify SPIONs via electrostatic interactions. PLL-SPIONs showed positive charges as reported previously (Riggio et al, 2012). In addition, it has been reported that no detectable uptake of iron was found for dextran-coated SPIONs with concentrations <0.5 mg/ml after 48 h incubation, and approximately half of the cells were abundantly labeled at 2 mg/ml (Dunning et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…The Fe nanoparticles tested were coated with inorganic surfactants; bio-compatible compounds (proteins, peptides, carbohydrates or zwitterionic agents) can effectively reduce their toxicity. Like in the case of poly-lysine coated magnetite particles, they show no observable toxic effects after 24 h dose on primary Schwann cells of the peripheral nervous system and human neuroblastoma cells (SH-SY5Y) 56 . Some cytotoxic effects of magnetic nanoparticles can be attributed to chemical coating and by-products and not directly to the metal core, although long term effects in neurons and brain are unknown.…”
Section: Discussionmentioning
confidence: 94%
“…One idea is to facilitate the uptake of magnetic NPs in regenerating neurons and their axons and to pull the axon along an external magnetic field. Therefore, the guidance of sprouting axons is promoted and the specificity of reinnervation is enhanced (Halpern, 2000 ; Riggio et al, 2012 ; Calatayud et al, 2013 ; Goya et al, 2014 ; Riggio et al, 2014 ). Previous studies showed initial success.…”
Section: Introductionmentioning
confidence: 99%
“…Human neuroblastoma (SH-SY5Y) cells were effectively influenced by an external magnetic field after magnetic NPs uptake. Also primary Schwann cells and olfactory ensheating cells showed satisfying uptake of NPs and could be moved along a magnetic field (Riggio et al, 2012 , 2013 ). Neurite orientation was shown to be directed toward a magnetic force after uptake of magnetic NPs into differentiated PC12 cells (Riggio et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%